Does TRIPS Drive to Productivity Growth in Indian Pharmaceutical Industry: A Non-parametric Analysis. Issue 2 (December 2017) - Singh, Jaswinder; Singh, Parminder
This article endeavours to analyse the inter-firm variations in total factor productivity growth (TFPG) of Indian pharmaceutical industry during the pre-Trade-Related Intellectual Property Rights (TRIPS) and post-TRIPS period by using non-parametric Malmquist productivity index (MPI). For analysis purpose, data for 30 major Indian pharmaceutical firms have been culled out from the various reports of the Centre for Monitoring Indian Economy (CMIE) during the period of 1991–2011. The empirical results reveal that the TFPG of the 30 major Indian pharmaceutical firms recorded to be 0.02 per cent and both the technological progress and efficiency change are equally contributing to the TFPG of the firms during entire study and pre-TRIPS period. It has been observed that TFPG has marginally regressed by 0.04 per cent in the post-TRIPS period and the negative growth of the average TFPG was contributed by technical inefficiency, whereas the positive technological progress helps to cover the impact of inefficiencies on TFPG. However, the growth of efficiency remains negative throughout the study period, which has been contributed both by the scale inefficiency and by the pure inefficiency, whereas the technological progress has a favourable impact on the productivity growth of the industry during the post-TRIPS period. Therefore, it can be inferred that the managerial, technical and scale inefficiencies in Indian pharmaceutical industry should be checked in order to operate at optimal scale and achieve potential productivity growth in the post-TRIPS period.